PEMETAAN KEBUTUHAN PENDIDIKAN NON FORMAL TERHADAP PEMUDA PUTUS SEKOLAH DI DESA MALLASORO KECAMATAN BANGKALA KABUPATEN JENEPONTO - Sriwulangdari, Sriwulangdari (LaGeografia, 2018)
This study aims to determine: 1) Characteristics of out-of-school youth; 2) Non Formal education required by youth dropping out of school; And 3) Mapping of non formal education needs to out of school youth. The population in this study were youth dropping out of school age 15-30 years while the sample in this study is the youth who have dropped out of school age 15-30 years amounted to 100 people. Data collection using interviews, documentation and observation, after data collected data analysis done by data reduction, mendisplay data, and draw conclusions. The results showed that: 1) Characteristics of youth drop out of school in terms of age most are age 27-30 years 41%, the number of siblings most is 3-4 people 32%, the largest number of household members is 5-6 people 39%, education level The highest formal achieved is the 53% SD level. Factors that cause drop outs are inadequate costs, marriage, interest in going to school, distance to school and help parents earn a living; 2) Non-formal education required by out-of-school youth is 36% sewing / 36% skill, 33% cooking / culinary skill, 11% goat farming skills, 9% crafting / handmaking skills, 4% woodworking skills, Computer 4%, facial / bridal make up 3%; And 3) Mapping of the need for non formal education to out-of-school youth indicates that out-of-school youth need non-formal education for their life needs. The types of skills that young people need to drop out of school are the types of sewing / dressing skills, cooking / culinary skills, goat farming skills, handicraft / wicker skills, woodworking skills, computer skills, and facial / bridal makeup skills.